Raíces Brewing Company : community, culture, cerveza - Thompson, Kenneth (London : SAGE Publications: SAGE Business Cases Originals, 2024)
This video case explores how three individuals, Tamil Maldonado Vega, José D. Beteta, and Martín D. Vargas, created a business that honors and shares their cultural roots. For years, wife and husband Mrs. Vega and Mr. Beteta, from Puerto Rico and Costa Rica respectively, focused on creating a strong community around their shared culture through grassroots organizing. However, they realized that they could not rely on donations and grants alone, and needed a sustainable means to support their efforts. The answer? A brewery, with a variety of libations crafted by Mr. Vargas, also from Puerto Rico, who serves as Head of Brewing Operations. Mr. Beteta draws on a background in business and IT as Chief Executive Officer. Mrs. Vega is the enthusiastic Chief Operating Officer. Together, the team provides focused direction to support arts and crafts in the community and ensure that their business is a family-friendly place that fosters and shares Latinx culture.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business planning -- Case studies; Family-owned business enterprises -- Case studies; Minority business enterprises -- Case studies